2015
DOI: 10.1177/0312896214541554
|View full text |Cite
|
Sign up to set email alerts
|

The pricing of idiosyncratic volatility: An Australian study

Abstract: This study examines the importance of idiosyncratic volatility in asset pricing for Australian stock returns from January 2002 to December 2010. Inspired by work from the early 1990s which found that portfolios constructed to mimic common risk factors explained significant variations in US stock returns, we construct an idiosyncratic volatility mimicking factor to explore the explanatory power of this factor in the Australian stock market. Our results indicate that (a) the idiosyncratic volatility mimicking fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
4
13
0
Order By: Relevance
“…Finally, study concludes that idiosyncratic volatility is an equally important factor similar to market, size and value factors in pricing Colombo stock exchange for the study sample period. The study findings are in line with Liu and Di Iorio [37] findings in Australian context. Hence, investor should compensate for holding idiosyncratic risk stocks in the portfolio.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, study concludes that idiosyncratic volatility is an equally important factor similar to market, size and value factors in pricing Colombo stock exchange for the study sample period. The study findings are in line with Liu and Di Iorio [37] findings in Australian context. Hence, investor should compensate for holding idiosyncratic risk stocks in the portfolio.…”
Section: Resultssupporting
confidence: 91%
“…Fama-MacBeth's cross-sectional regression of two-factor, three-factor, and four-factor model with idiosyncratic volatility factor found that idiosyncratic volatility is negatively related to the expected portfolio returns for MC-and IVOL-based portfolios, whereas idiosyncratic volatility is positively related to the expected portfolio returns for PBbased portfolio. Market return is also important factor that explains risk return relationship, and it is related negatively to the excepted portfolio returns for all MC-and PB-based portfolios, whereas it is positive for IVOL-based portfolios, and findings are similar to Liu and Di Iorio [37] findings in Australian context. Fama-MacBeth's cross-sectional regression confirms that three-factor model with idiosyncratic volatility is equally significant as Fama-French's three-factor model in explaining risk return relationship.…”
Section: Fama-macbeth's Cross-sectional Regression Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…They caution that the idiosyncratic volatility puzzle documented in developed markets may not apply to emerging stock markets. In a recent study, Liu and Di Lorio () find a positive relation between idiosyncratic volatility and stock average returns for Australian stocks. In sum, prior studies focus mainly on errors‐in‐variable and measurement error problems as empirical explanations for the Ang et al .…”
Section: Introductionmentioning
confidence: 96%
“…They caution that the idiosyncratic volatility puzzle documented in developed markets may not apply to emerging stock markets. In a recent study, Liu and Di Lorio (2015) find a positive relation between idiosyncratic volatility 1 In value-weighted portfolios, winner stocks receive heavier weighting than loser stocks, such that return reversal by winner stocks overshadow that of loser stocks. This causes low subsequent value-weighted return.…”
mentioning
confidence: 97%